Variations in Vaginal, Penile, and Oral Microbiota After Sexual Intercourse: A Case Report - Carda-Diéguez, Miguel; Cárdenas, Nívia; Aparicio, Marina; Beltrán, David; Rodríguez, Juan M.; Mira, Alex (Frontiers in Medicine, 2019)
•Background: Bacterial vaginosis is the most common infection in women and it has been proved that dysbiosis of vaginal microbiota can promote the infectious status. This case report shows the effect of oral and vaginal sex over the microbiota of a heterosexual couple who reported repeated problems of vaginal and oral infections after sexual intercourse. •Case presentation: A woman (32) reported to have vaginal infections and gingivitis after she had started a relationship with a man (34) and associated them with unprotected sex. No treatments successfully removed the problem and it repeated every time they had sexual encounters. Vaginal, penile and oral swabs were collected before and after sexual encounters in order to analyze changes in the respective microbiotas. DNA was extracted from all samples and the bacterial 16S rRNA gene was sequenced using Illumina MiSeq. •Conclusions: Lactobacillus occupied the great majority of the vaginal microbiota in all scenarios except after unprotected sex, which caused a bacterial dysbiosis that lasted at least for a week. Similarly, the penile microbiota changed significantly after unprotected sexual relationships. Interestingly, both oral and vaginal sex increased the abundance of Lactobacillus in the male oral and penile microbiota, respectively. In conclusion, unprotected sexual intercourse influenced the genital microbiota in the couple studied and future studies with larger sample sizes should study if sex may be a factor promoting vaginal infection through dysbiosis and hampered protection by the resident microbiota.